Effect of Lamotrigine on Prophylaxis of Pediatric Classic Migraine - Mirzaei, M.G.R.; Azimian, M.; Moezzi, M.; Vameghi, R.; Rafieian-kopaei, M. (Iranian Journal of Child Neurology, 2009)
Objective This study was conducted to evaluate the preventive effect of lamotringine on migraine aura and migraine attacks in children, afflicted with classic migraine. Material & Methods Conducted between October 2005 and April 2008 in the neurology clinic of Kashani hospital, Shahrekord, this study was a clinical trial, aimed at evaluating the prophylactic effects of Lamotringine administered to 21 children suffering from migraine with aura. Results Of the subjects, 52.4% of patients were female. The most common type of aura was visual (42.9%). Following use of Lamotrigine, significant reductions were seen in the frequency (from 5 ± 0.83 to 3.04 ± 1.65) and in intensity (from 6. 33 ± 1.08 to 3.66 ± 1.1) of migraine aura (P= 0.002). After 6 months of drug usage 66.6% of patients were improved. Conclusion Lamotringine is effective in reducing the migraine aura and intensity of attacks in patients suffering from migraine with aura, and is hence beneficial for prophylactic therapy in children with classic migraine.